Cu(II) complex heterogenized on magnetic mesoporous nanocomposite (SBA-16@Fe3O4) as an efficient catalyst for the reduction of nitro compounds - Yuanlin Shi (Journal of Saudi Chemical Society)
In the present study, a novel magnetic heterogeneous copper catalyst was developed by the immobilization of a Cu(II) complex on the surface of magnetic mesoporous nanocomposite (SBA-16@Fe3O4) through post-synthetic method. The synthesized catalyst was analyzed by various characterization methods including FT-IR, EDS, XRD, Nitrogen physisorption, TEM, TGA, VSM, and ICP-OES. After complete characterization, its catalytic efficiency was evaluated in the hydrogenation of nitroarenes to amines. Taking the nitrobenzene reduction of as an example of a reaction, the reaction conditions were optimized by changing diverse parameters like solvent, temperature, time, amount of catalyst, as well as the type and amount of hydrogen source. The catalyst revealed highly efficient catalytic activity in the hydrogenation of numerous nitroarenes to the corresponding aminoarenes in pure water as the solvent with sodium borohydride as a H2 source at room temperature. Additionally, the catalyst could be simply recovered from the mixture of reaction via magnetic separation and was able to mediate the reaction for multiple times with undiminished catalytic performance.